(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of treatment management and some factors associated with relapse among patients with schizophrenia in primary healthcare settings in Western Hai Phong, Vietnam, 2026. Methods: A cross-sectional study was conducted on 433 patients. Data were collected through structured interviews and medical record review. Descriptive statistics, Chi-square tests, and univariate odds ratios (OR) with 95% confidence intervals (CI) were applied. Results: The proportion of patients under regular management was 86.9%, while 87.8% received home-based follow-up care and 48.0% were supervised for medication intake. The relapse rate within the past 12 months was 9.9%. No significant association was found between relapse and gender or age (p>0.05). Patients with a treatment duration of ≥40 years had a higher relapse rate compared to those treated for <20 years (OR=4.02; 95%CI:1.25–12.98; p<0.05). Patients under medication supervision had higher relapse rates; however, this finding should be interpreted cautiously because of possible reverse causation. Conclusion: The management and treatment of patients with schizophrenia at the primary healthcare level achieved positive outcomes. However, further strengthening of medication supervision and improvement in the quality of patient management remain necessary.